Efectos del etanol en la expresión génica de ɑ-sinucleína en células cancerígenas. (2020)
The chronic use of alcohol has been associated with significant changes in the expression of α-synuclein, altering the reward system and generating neuronal and mitochondrial damage. There are very few treatments for this disease and the results are modest, so your study is necessary for the development of new therapies. The objective of this study was to determine the effect of low doses of ethanol in cancer cells with different dosage schedules and to determine the rate of expression of the gene α-synuclein. It shows that there is a decrease in the expression of α-synuclein in the treatments with ethanol.